Swyer syndrome: Reports of 2 cases (BIRDEM Medical Journal, 2016)
Swyer syndrome is a form of pure 46 XY gonodal dysgenesis in which individuals have male chromosomal pattern (46XY) but a female phenotype. One out of five women with the Swyer syndrome have a deletion in the DNA-binding region of the SRY gene, while in the remaining 8090% of cases, the SRY gene is normal and mutations in other testis determining factors are probably implicated. Early diagnosis is crucial for a number of reasons: first, the risk of gonadal malignancy, second, the early institution of estrogen therapy for induction of puberty and third, to allow for adequate hormone replacement to improve bone mineral density. We present two cases of Swyer syndrome with different presentationBirdem Med J 2016; 6(1): 50-53